The Characteristics of Motherhood through Mother in Michael Lloyd Green’s I Am Mother - Elisa Wakhidatul Safitri; Cahyaningsih Pujimahanani (PT. Gudang Pustaka Cendekia, 2025)
This research title explores the characteristics of motherhood as represented by the character Mother in Micahel Lloyd Green’s I Am Mother. The research focuses on one of the characteristics is nurturing. This research using a qualitative film analysis approach and obtain the data from the movie script. The findings demonstrate that the character Mother in I Am Mother embodies aspects of motherhood through the characteristic of nurturing behavior by providing food, education, protection, and guidance for Daughter’s development additionally, Mother’s strict control and manipulation of Daughter add complexity to the definition of ideal caregiving. This research concludes that I Am Mother reconstructs the concept of motherhood by integrating human and technological elements. The film suggests that nurturing is not limited to biological mother but can also be fulfilled by artificial intellegence.